Sex differences in echocardiographic predictors of bradycardia detected by implantable loop recorder in patients with syncope and palpitations. Issue 7 (26th May 2021) - Falsing, Mathilde Musoni; Brainin, Philip; Andersen, Ditte Madsen; Larroudé, Charlotte Ellen; Lindhardt, Tommi Bo; Ravnkilde, Kirstine; Modin, Daniel; Karsum, Emil Høegholm; Gislason, Gunnar; Biering‐Sørensen, Tor
Abstract: Objective: Our aim was to investigate whether echocardiography may aid in identifying patients, specifically men, at risk of bradycardia as detected by implantable loop recorders (ILR) in patients evaluated for syncope and palpitations. Methods: We included ambulatory patients undergoing ILR implantation for syncope (84%), presyncope (9%), and palpitations (8%). Echocardiographic examination was performed prior to implantation (2.9 months [IQR 1.0–6.0 months]). Echocardiograms were analyzed for conventional and speckle tracking parameters. We examined time to first event of bradycardia, defined as (a) heart rate <30 beats/min and (b) ≥4 beats, including sinus arrest, asystole, sinoatrial block, and second‐ and third‐degree atrioventricular nodal block. We applied Cox proportional hazards models. Results: A total of 285 patients we enrolled, and during a median time of 2.7 years [IQR 1.0, 3.3 years] of continuous heart rhythm monitoring, 84 (29%) had bradycardia detected by ILR. Patients with bradycardia were older (61 ± 19 years vs 55 ± 18 years, P  = .01) and more frequently men (62% vs 44%, P  = .01). Sex modified the association between echocardiographic parameters and bradycardia ( P interaction <0.05 for all), such that left ventricular LV mass index (HR: 1.02 per 1g/m 2 increase [1.01‐1.04], P  < .001), LV ejection fraction (HR: 1.04 per 1% decrease [1.01‐1.08], P  = .02), and global longitudinal strain (HR: 1.09 per 1% decrease [1.01‐1.19], P  = .03) were associated with bradycardia in men but not women ( P  > .05 for all in female). After adjusting for baseline clinical characteristics, medical therapy, and loop indication, the abovementioned parameters remained significantly associated with incident bradycardia in men. Conclusion: Echocardiographic parameters of LV structure and function may potentially be more useful for predicting bradycardia in men than women, among patients undergoing ILR implantation for syncope, presyncope, and palpations.